2016
DOI: 10.1128/iai.00074-16
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation by Giardia duodenalis Parasites through the Lectin Pathway Contributes to Mast Cell Responses and Parasite Control

Abstract: Infection with Giardia duodenalis is one of the most common causes of diarrheal disease in the world. While numerous studies have identified important contributions of adaptive immune responses to parasite control, much less work has examined innate immunity and its connections to the adaptive response during this infection. We explored the role of complement in immunity to Giardia using mice deficient in mannose-binding lectin (Mbl2) or complement factor 3a receptor (C3aR). Both strains exhibited delayed clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 63 publications
4
28
0
1
Order By: Relevance
“…Our data confirm a previous report (83) demonstrating that PE MCs do not express C3aR at steady-state, although functional studies suggest that C3a activates MCs from skin and the small intestine (84,85). In line with this notion, variable and complex C3aR expression has been shown in human MCs.…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirm a previous report (83) demonstrating that PE MCs do not express C3aR at steady-state, although functional studies suggest that C3a activates MCs from skin and the small intestine (84,85). In line with this notion, variable and complex C3aR expression has been shown in human MCs.…”
Section: Discussionsupporting
confidence: 92%
“…[58] reported a delay in the clearance of Giardia parasites and recruitment of mast cells to the small intestine in mice lacking MBL or complement component C3a receptor (C3aR). Furthermore, mice lacking C3aR also exhibited significantly reduced T-cell responses against parasite antigens following infection but IgA levels within the small intestine were unaffected [58]. Taken together, these results indicate a role for the complement system in not only activating but also mediating downstream immune responses during infection.…”
Section: Protective Immunity Towards Giardiamentioning
confidence: 99%
“…Additionally, it would be interesting to understand if mast cell-derived IL-6 is critical to Th17 cell development. Li et al [88] found a reduction in IL-17 responses in the absence of signaling via C3aR, which suggest that a decrease in mast cell recruitment also correlates with decreased IL-17 production. In human patients that have recovered from Giardia , IL-17 has been found to be upregulated when effector memory CD4 + T-cell are restimulated with Giardia antigen [89]; in addition, several studies [25, 87, 90, 91] reported the upregulation of IL-17 during murine or bovine infections, and delayed parasite clearance in IL-17 knockout mice has also been reported [87, 90].…”
Section: Protective Immunity Towards Giardiamentioning
confidence: 99%
“…Mast cell deficient c-kit w/wv (c-kit dependent deficiency in the mast cell compartment) mice and c-kit depleted mice both failed to control a Giardia infection [26], suggesting that mast cells and c-kit dependent mechanisms are necessary for elimination of a G. intestinalis infection. In addition, the complement factor 3a receptor was found to be important for recruitment of mast cells to the mucosa during Giardia-infections in mice [27]. There was also an effect on the adaptive immune system since mast cell-deficient mice failed to produce parasite-specific IgA [26].…”
mentioning
confidence: 99%